2018
DOI: 10.1186/s40463-018-0298-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of cell cycle-associated proteins p16, pRB, cyclin D1 and p53 in resected oropharyngeal carcinoma

Abstract: BackgroundHuman papillomavirus (HPV)-related oropharyngeal squamous cell carcinoma (OPSCC) has an improved outcome and may allow for treatment de-escalation. High-risk HPV (HR-HPV) infection is associated with deregulated expression of the cell cycle-associated proteins p16INK4, pRB, cyclin D1 and p53. The objective of this study was to assess cell cycle proteins as potential surrogate markers for HR-HPV DNA testing to identify OPSCC with favorable prognosis after resection.MethodsTissue microarray cores of 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
(41 reference statements)
0
17
1
Order By: Relevance
“…Given that cyclin D1 is required for tumor formation induced by HPV proteins E6 and E7 [52], it indicated that cyclin D1 downregulation may also contribute to a better prognosis of HPV(+) patients. Indeed, previous studies have associated low cyclin D1 expression in HPV(+) tumors with improved survival rates when in combination with high p16 INK4a , low pRb and low p53 [53,54]. However, we have not observed an improved outcome in HPV(+) patients who exhibit low expressions of cyclin D1 mRNA.…”
Section: Discussioncontrasting
confidence: 78%
“…Given that cyclin D1 is required for tumor formation induced by HPV proteins E6 and E7 [52], it indicated that cyclin D1 downregulation may also contribute to a better prognosis of HPV(+) patients. Indeed, previous studies have associated low cyclin D1 expression in HPV(+) tumors with improved survival rates when in combination with high p16 INK4a , low pRb and low p53 [53,54]. However, we have not observed an improved outcome in HPV(+) patients who exhibit low expressions of cyclin D1 mRNA.…”
Section: Discussioncontrasting
confidence: 78%
“…Sensitivity of p16 immunostaining in the oropharynx is around 80–90% ( 8 , 62 , 63 , 70 , 71 , 81 , 82 , 87 , 88 , 92 95 ). One study compared the performances of p16 immunostaining according to the threshold of positivity used to assess p16 immunostaining positivity ( 96 ).…”
Section: Main Techniques Used To Detect Hpv In Opsccmentioning
confidence: 99%
“…Further studies led in different OPSCC populations and comparing different thresholds of positivity are required. Considering that specificity of p16 immunostaining varies from 80 to 90% ( 8 , 62 , 63 , 70 , 71 , 81 , 82 , 87 , 88 , 92 95 ), some patients with OPSCC may be diagnosed as having a transcriptionally active HPV infection when it is not the case. Rietbergen et al showed especially that OPSCCs with a p16 immunostaining, and no transcripts of E6 and E7 proteins have a poorer prognosis compared to those with E6 and E7 transcripts ( 86 ).…”
Section: Main Techniques Used To Detect Hpv In Opsccmentioning
confidence: 99%
“…Some of the mutated genes frequently associated with HNSCC are TP53 , CDKN2A , FAT1 , NOTCH1 , EGFR, HRAS , and PI3KCA [23,24,25,26,27], and the mutations in these genes are recognised as drivers of tumour development and progression. In HPV + subtype patients, high-risk HPV infection has been associated with the abnormal expression of proteins associated with cell cycle regulation, including p53 and p16 (CDKN2A) [21,28,29]. Functional TP53 inhibits the mammalian target of rapamycin (mTOR) pathway through AMPK in response to cellular stresses and DNA damage [21].…”
Section: Genomic Alterations In Head and Neck Cancermentioning
confidence: 99%